Biomass Burning Is a Non‐Negligible Source for Ammonium During Winter Haze Episodes in Rural North China: Evidence From High Time Resolution 15N‐Stable Isotope. Issue 3 (3rd February 2023) - Feng, Xinxin; Chen, Yingjun; Du, Huiyun; Feng, Yanli; Mu, Yujing; Chen, Jianmin
Abstract: The refined source apportionment of ammonium (NH4 + ), especially for biomass burning emissions, is unclear. Hourly resolution δ 15 N‐NH4 + values for three winter haze episodes (EP1–EP3) were determined in the North China Plain (NCP) in 2019 to identify and quantify the contribution of biomass burning. A reasonable source‐resolved structure of NH4 + was obtained after using the corrected source signatures of 15 N and considering biomass burning emissions. The time‐series variation in biomass burning and vehicle sources identified by δ 15 N was more reasonable and matched better with their tracers (e.g., levoglucosan). The non‐negligible contribution of biomass burning in the NCP was found and contributed 13.0% ± 11.4% to NH4 + in haze episodes, but in special stages was as high as 29% ± 11% in local emission of EP1 and 23% ± 15% in southwest transportation of EP2. The redistribution of NH4 + sources further emphasize the contribution of biomass burning to haze episodes, as its contribution to PM2.5 increased up to 5% (without considering SO4 2− and NO3 − ). Considering NH4 + uniqueness in the formation of new particles, the role of biomass burning during haze episodes should be considered. This study indicates that further studies need to be conducted to reduce biomass burning emissions in the NCP. Plain Language Summary: The source contributions of ammonium (NH4 + ) during winter haze episodes were not unclear. This study investigated the source apportionment of NH4 + during three haze episodes in the North China Plain (NCP) in 2019 by high time resolution 15 N technique to quantify the emission source contributions, especially for biomass burning emission. Results found that a reasonable source contribution of NH4 + were obtained when the corrected 15 N source signatures and biomass burning emission were considered. Specially, the contributions of biomass burning to NH4 + accounted for 13% during the entire sampling periods, and showed higher ratios (23%–29%) in special transmission channels in haze episodes. In addition, the redistribution of NH4 + sources further emphasize the contribution of biomass burning to haze episodes with its contribution to PM2.5 increased up to 5%. These findings showed that biomass burning was non‐negligible contribution sources to NH4 + and PM2.5 during haze episodes, which should be paid more attention to reduce its emission in the NCP. Key Points: Reasonable source‐resolved structure of NH4 + was obtained using corrected 15 N source signatures and considering biomass burning emissions The contribution of biomass burning identified by δ 15 N showed the similar variation with its tracer levoglucosan Biomass burning from the local and southwest transmission channels of Hebei Province showed an outstanding contribution to NH4 +